2011
DOI: 10.1007/s00296-011-2182-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin and neuropeptide Y concentrations in patients with rheumatoid arthritis treated with infliximab, a TNF-α antagonist

Abstract: TNF-α is one of the key proinflammatory cytokines in pathogenesis of rheumatoid arthritis (RA). TNF-α was also found to enhance synthesis of leptin. Leptin is mainly adipocyte-derived hormone controlling appetite and energy expenditure. It acts through inhibition of neuropeptide Y secretion. It is possible that TNF-α-induced leptin secretion contributes to body mass reduction in patients with RA. The study was designed to determine the influence of inactivation of the TNF-α with infliximab on plasma leptin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
22
1
1
Order By: Relevance
“…They were positively correlated with the BMI and waist circumference Kopec-Medrek et al [20] 2012 n.a. assessed further by a third investigator (Dian Zhou), and a final decision was made by the majority of the votes.…”
Section: Nomentioning
confidence: 93%
See 3 more Smart Citations
“…They were positively correlated with the BMI and waist circumference Kopec-Medrek et al [20] 2012 n.a. assessed further by a third investigator (Dian Zhou), and a final decision was made by the majority of the votes.…”
Section: Nomentioning
confidence: 93%
“…Targonska-Stepniak et al [95] reported that serum leptin levels were higher in patients with erosive RA. However, some studies have reported that serum leptin levels of RA patients were not different from controls [20,25,33,38], and were concerned significantly with body mass index (BMI) but not disease activity stage (DAS) [33,39]. Anders et al observed that leptin serum levels are not correlated with disease activity in RA patients [40].…”
Section: Leptin Levels In Serum Synovial Fluid and Synovial Tissue Amentioning
confidence: 99%
See 2 more Smart Citations
“…The pathomechanisms for the body mass reduction that occurs in patients with chronic inflammatory diseases remains unclear (Kopec-Medrek et al 2012).…”
Section: Introductionmentioning
confidence: 99%